Salón Socio-Cultural Entre Palmas - Osorio Garcia, Juan Jose (Universidad Antonio Nariño, 2023)
Throughout history it has become evident that the Indigenous communities of Colombia have been abandoned, violated and marginalized by the Colombian State, being the main victims of oblivion, violence and the absence of public investment. This generated a greater problem that is the risk of disappearance of many communities, due to the loss of ancestral knowledge, autochthonous techniques and collective memory. The Las Palmas Indigenous Reservation in Coyaima-Tolima is in this situation, which presents problems in the quality of the meetings of the Indigenous Council, due to the place where they meet, the construction